Integrasi Asuransi Syariah, Maqasid al-Shariah, dan Circular Economy Dalam Mewujudkan Keuangan Islam Berkelanjutan - Soeharjoto Soeharjoto; Debbie Aryani Tribudhi; Dewi Nurri Setiawati; Ria Arni Fajriah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Sustainable development is global agenda for right now. This is in line with the increasing environmental crisis, social inequality, and economic instability. Concept of a circular economy was developed to improve resource efficiency, reduce waste, and promote economic and environmental sustainability. From Islamic economic perspective, principles of sustainability, justice, and public interest have become part of the development goals formulated in the maqasid al-shariah. The novelty of this research lies in its integrative conceptual framework, which positions sharia insurance as a link between the normative values of maqasid al-shariah and the practical implementation of a circular economy. Aims of this research is to analyze the conceptual link between Islamic insurance, maqasid al-shariah, and the circular economy in building a sustainable Islamic financial framework. Research method uses a literature study with a normative conceptual approach to Islamic economic theory, sustainable finance, and the circular economy. The analysis was conducted by examining the main principles of Islamic insurance, particularly ta'āwun, justice, and collective risk management, and their relevance to the goals of maqasid al-shariah and the circular economy. Research findings indicate a strong alignment between the principles of Islamic insurance and the values of the circular economy and maqasid al-shariah. The integration of the three has the potential to strengthen social and economic resilience, promote the development of green investment, and expand the role of Islamic finance in supporting sustainable development. Therefore, sharia insurance can be used as an instrument to support economic sustainability based on Islamic values.